Human Blood CD1c+ Dendritic Cells Promote Th1 and Th17 Effector Function in Memory CD4+ T Cells - Leal Rojas, Ingrid M.; Mok, Wai-Hong; Pearson, Frances E.; Minoda, Yoshihito; Kenna, Tony J.; Barnard, Ross T.; Radford, Kristen J. (Frontiers in Immunology, 2017)
Dendritic cells (DC) initiate the differentiation of CD4+ helper T cells into effector cells including Th1 and Th17 responses that play an important role in inflammation and autoimmune disease pathogenesis. In mice, Th1 and Th17 responses are regulated by different conventional (c) DC subsets, with cDC1 being the main producers of IL-12p70 and inducers of Th1 responses, whilst cDC2 produce IL-23 to promote Th17 responses. The role that human DC subsets play in memory CD4+ T cell activation is not known. This study investigated production of Th1 promoting cytokine IL-12p70, and Th17 promoting cytokines, IL-1β, IL-6 and IL-23, by human blood monocytes, CD1c+ DC, CD141+ DC and plasmacytoid DC and examined their ability to induce Th1 and Th17 responses in memory CD4+ T cells. Human CD1c+ DC, produced IL-12p70, IL-1β, IL-6 and IL-23 in response to R848 combined with LPS or poly I:C. CD141+ DC also capable of produced IL-12p70 and IL-23 but were not as proficient as CD1c+ DC. Activated CD1c+ DC were endowed with the capacity to promote both Th1 and Th17 effector function in memory CD4+ T cells, characterized by high production of IFNγ, IL-17A, IL-17F, IL-21 and IL-22. These findings support a role for CD1c+ DC in autoimmune inflammation where both Th1 and Th17 responses play an important role in disease pathogenesis.